Pengaruh Kualitas HP Samsung terhadap Permintaan Konsumen pada Konter Online Celuler - Bahagia, Sonya Tivany; Timisela, Yanti Marlina; Jantje, Hendry J (Attractive : Innovative Education Journal, 2022)
This study aims to analyze the influence of the quality of Samsung cellphones on consumer demand at cellular online counters. The data analysis method used is quantitative analysis. significant test through (t-test), using simple linear regression and coefficient of determination (R2). The population in this study are all consumers who use HP Samsung at Cellular Online Counters. The sample is 82 respondents. Primary data were obtained through interviews, questionnaires and documentation studies. From the results of data processing simple linear regression analysis using the SPSS for windows version 25 program, the regression equation Y = 5.577 + 0.837X, the regression coefficient value of 0.837 means that every time there is a change and an addition of one percent in the Samsung HP quality variable, the Consumer Demand variable will increases by 0.837 if the quality variable of Samsung HP is zero, then Consumer Demand has a value of 5.557. In the coefficient of determination test, R square is 61.3%, meaning that the quality of Samsung's cellphones has an effect on consumer demand by 61.3%, while the remaining 38.7% is influenced by other factors not analyzed in this study. The results of the t test, where t count 11.262 > t table 1.6641, it can be said that the quality variable of Samsung HP has a positive and significant effect on consumer demand. Keywords: Samsung HP Quality, Consumer Demand, Handphone Quality